Frequency of Surgical Site Infection after Open Appendectomy using Antimicrobial Sutures - gul, Ayesha; Ahmed, Raheel; Kazim, Erum; Kumar, Dileep; Zulfikar, Imrana (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To determine the frequency of Surgical Site Infection after open appendectomy using antimicrobial sutures. Methodology: Present study design was prospective case series conducted after the approval from the Research, Training and Monitoring Cell of CPSP in Department of Surgery, Dr.Ruth K.M Pfau, Civil Hospital Karachi/ Dow University of Health Sciences Karachi from December 2017 to May 2018 with non-probability sampling technique. All patients between the age of 15-40 years of either sex who visited the Emergency Department and were diagnosed clinically with acute appendicitis were included in the study. Patients with generalized peritonitis or per-operative findings of malignancy, perforation, or gangrenous appendix were not enrolled. Open appendectomy was carried out in all patients, antimicrobial coated sutures were used throughout the surgery, and the patient was kept under follow-up for 3 months in surgical OPD to detect any clinical feature of SSI. The data was analyzed using SPSS version 17. Results: Among 139 studies cases, 76 (54.68%) were male, and 63 (45.32%) were females with a male to female ratio of 1.2:1. The age range was from 15 to 40 years with a mean age of 27.23±5.97 years. The majority of the patients, 88 (63.31%), were between 15 to 30 years of age. In this study, frequency of SSI after appendectomy using antimicrobial coated suture was found in 14 (10.07%) patients. Conclusion: The results demonstrate that the frequency of surgical site infection after incorporating antimicrobial sutures (Triclosan) is not significantly different statistically as expected in clean-contaminated abdominal surgery. Keywords: Acute appendicitis, antimicrobial coated sutures, open appendectomy, surgical site infection.